2015
DOI: 10.12816/0040865
|View full text |Cite
|
Sign up to set email alerts
|

Urticarial Vasculitis Following Exposure to Holi Colors : A Rarity

Abstract: Holi is a festival of colours, traditionally celebrated by greeting others and applying various colours. These colours are synthetic dyes which may have harmful side-effects on the skin and mucocutaneous areas like the conjunctiva and oral mucosa. In India, these colours are prepared on a small scale and lack any quality checks. Here we present a case of a 43 years old female who developed angioedema with urticaria progressing into urticarial vasculitis after playing with the colours in the festival of Holi. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Empirical investigations have confirmed that these may result in skin abrasions, irritation of the skin and eyes, allergies, and even asthma attacks (Rawat, 2008, Sharma and Saxena, 2013 [1,2,3] . Jain et al (2015) [7] reported that these artificial dyes used for Holi are likely to cause negative effects on the skin, including the mucosa of the mouth and conjunctivitis. Das et al (2015) [8] reported that synthetic Holi powder includes sand, soil, and heavy metals, is utilized annually during the Holi festival which can do harm to the environment and to people's health, Thus a straightforward, inexpensive process for producing environmentally safe Holi powder needs to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical investigations have confirmed that these may result in skin abrasions, irritation of the skin and eyes, allergies, and even asthma attacks (Rawat, 2008, Sharma and Saxena, 2013 [1,2,3] . Jain et al (2015) [7] reported that these artificial dyes used for Holi are likely to cause negative effects on the skin, including the mucosa of the mouth and conjunctivitis. Das et al (2015) [8] reported that synthetic Holi powder includes sand, soil, and heavy metals, is utilized annually during the Holi festival which can do harm to the environment and to people's health, Thus a straightforward, inexpensive process for producing environmentally safe Holi powder needs to be established.…”
Section: Introductionmentioning
confidence: 99%